If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 3y = -10 Solving -7x + 3y = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. -7x + 3y + -3y = -10 + -3y Combine like terms: 3y + -3y = 0 -7x + 0 = -10 + -3y -7x = -10 + -3y Divide each side by '-7'. x = 1.428571429 + 0.4285714286y Simplifying x = 1.428571429 + 0.4285714286y
| (2z-1)(4z-3)=0 | | -5+y=.3y+4.1 | | 5x^3-2x^2+3x-17=y | | 5x^3-2x^3+3x-17=y | | (5y+4)-(2+4y)=3 | | 7(d^2-4)=0 | | 7d^2-28=0 | | 15d-32=-92 | | 31=4a-9 | | 3y=54-9x | | -4/7w=-20 | | 3x-36=2y | | 100b+110a-ab=370 | | -19d=0 | | 7x-3+3x=-10x-3 | | 7d^2+5d-(5d+20)-8=0 | | 11a+10b=370 | | -x^2=81 | | 3x+8x-12=8x+1 | | x-4sqrtx=12 | | 10(t-6)+5t=5(3t+3)-9 | | 2x-5x=30 | | x^3-27t^3=0 | | 7+2z-3=9z+4-6z | | 20=-z | | 250x^3-2=0 | | 4(3w)=-48 | | -(7xy-10)+3(4xy+8)= | | (X+40)+x=360 | | 0=60x^4+60x^3-60x^2 | | y=60x^4+60x^3-60x^2 | | f(x)=14x+9 |